The Kaunas Second Auxiliary Police Service Battalion and the Massacre in Belarus in 1941–1943 - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2007)
During the years of the German occupation (1941–1944) military-police units under the jurisdiction of the Nazis, which were called auxiliary police service, security, self-preservation battalions and other names, were formed. Some of the Lithuanian military-police formations took part in the killings in Lithuania, Belarus and Ukraine. In Kaunas in August 1941 the Second Auxiliary Police Service Battalion was formed (leader Major A. Impulevičius), which together with the German Eleventh Reserve Police Battalion was sent by the Nazis to the Minsk district in Belarus to fight against Soviet partisans. All together, there were 485 troops, commissioned and non-commissioned officers. About 450 troops of the Lithuanian battalion, all three companies, participated in the killings.